INFLUENCE OF CULTIVATION OF CHLORELLA VULGARIS ON MICROORGANISMS IN SEAFOOD WASTEWATER - Dong Phuong, Nguyen Thi; Ngoc Thu, Tran Thi; Van Anh, Le Thi; Phuoc Trang, Nguyen Huu (Vietnam Journal of Biotechnology, 2018)
Microalgae cultivation in wastewater for many purposes has been investigated recently decade ago. In this study, Chlorella vulgaris was chosen to culture for examination of its influences on microorganisms of seafood wastewater in particular aerobic bacteria, Coliform and E. coli. The microalgae cultivation was realized in Erlenmeyer flasks containing seafood wastewater medium. Another was also grown in original medium called Sueoka medium for control. All experiments were set up until almost all Chlorella vulgaris decanted or flocculated in the bottom of flasks. The changes of bacteria counts including aerobic bacteria, Coliform and E. coli were measured to evaluate the impact of cultivation of Chlorella vulgaris on them in this sewage. Otherwise, the growth of microalgae has been also recorded for evaluating the effect of a new medium on metabolism of Chlorella vulgaris. The results showed that the bacteria counts were significantly reduced after day 3 of microalgae culture. These results have been calculated the efficiency of aerobic bacteria, Coliform and E. coli elimination out of wastewater medium represented approximately 70%, 81% and 90% respectively. These eliminations provided evidences of difficult metabolism of bacteria under the presence of microalgae as like as Chlorella vulgaris. In other words, the symbiosis of microalgae and bacteria in sewage could prevent the raising of bacteria counts.